Profil Penderita Morbus Hansen di Rawat Inap RSUP Prof. Dr. R. D. Kandou Manado Periode 2016-2018 - Makalew, Deivy A.; Kapantow, Grace M.; Pandaleke, Herry E. J. (e-CliniC, 2020)
Abstract: Morbus Hansen (MH) is a chronic infectious disease caused by Mycobacterium leprae. World Health Organization data showed that in 2018, Indonesia was the third rank in the world with incidences of 17,017 cases. This study was aimed to determine the profile of MH patients at Irina F-Dermatovenereology of Prof. Dr. R. D. Kandou Hospital. This was a descriptive retrospective study by evaluating medical record files of MH patients hospitalized at Irina F-Dermatovenereology, Prof. Dr. R. D. Kandou Hospital from 2016 to 2018. The results showed that the distribution of MH patients in 2016-2018 was 14 patients, 20 patients, and 18 patients respectively. Most patients were in the age group of 25-34 years (38.46%). Males were more common than females (4.8:1). Most patients were from Manado. All patients had multibacillary (MB) type MH and ENL was the most common reaction (86.54%). The comorbidities were gastrointestinal disorders, electrolyte imbalance, and anemia. In conclusion, the number of hospitalized MH patients was slightly increased from 2016 to 2017 and then was decreased insignificantly in 2018. Most patients were male, in the age group of 25-34 years, came from Manado, multibacillary type MH, had ENL reaction and comorbidity of gastrointestinal disorders.Keywords: Morbus Hansen, hospitalized patientsÂ Abstrak: Morbus Hansen (MH) merupakan penyakit infeksi kronik yang disebabkan oleh Mycobacterium leprae. Data World Health Organization (WHO) pada tahun 2018 menunjukkan bahwa Indonesia menempati peringkat ketiga di dunia dengan jumlah kasus baru mencapai 17.017 kasus. Penelitian ini bertujuan untuk mengetahui profil penderita MH di Irina F Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialaht deskriptif retrospektif dengan cara mengevaluasi berkas rekam medis penderita MH yang dirawat inap di Irina F Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado pada periode 2016-2018. Hasil penelitian mendapatkan distribusi penderita MH pada tahun 2016 sebanyak 14 pasien, tahun 2017 sebanyak 20 pasien, dan tahun 2018 yaitu 18 pasien. Kelompok usia terbanyak ialah 25-34 tahun (38,46%). Penderita laki-laki lebih banyak dibandingkan perem-puan (4,8:1). Penderita terbanyak berasal dari Kota Manado. Semua penderita memiliki MH tipe Multibasiler (MB). Reaksi ENL merupakan tipe reaksi yang terbanyak (86,54%). Penyakit penyerta yang banyak didapati ialah gangguan gastrointestinal, gangguan elektrolit dan anemia. Simpulan penelitian ini ialah penderita MH yang dirawat inap mengalami peningkatan dari tahun 2016 sampai 2017, sedikit menurun pada tahun 2018 namun tidak bermakna. Penderita yang terbanyak ialah kelompok usia 25-34 tahun, jenis kelamin laki-laki, asal Kota Manado, MH tipe Multibasiler (MB), reaksi tipe ENL, penyakit penyerta gangguan gastrointestinal.Kata kunci: Morbus Hansen, pasien rawat inap